Analyzing the Influence of Productivity, Price, and Population on Indonesia's Food Security: A Study from an Islamic Economic Perspective (2013-2022) - Munajahro, Violanida; Nurlaili; Sari, Yetri Martika (CV. SPDF Harmony, 2025)
Background: Food security is a major concern in Indonesia’s economy, influenced by agricultural productivity, food prices, and population growth. Instability in food supply and price fluctuations threaten national food security. An Islamic economic perspective offers additional insights, emphasizing justice and equitable food distribution.Aims: This study aims to analyze the impact of agricultural productivity, food prices (especially rice), and population size on Indonesia’s food security from 2013 to 2022, using an Islamic economic framework to generate policy recommendations for sustainable food security.Methods: A quantitative approach is used with time-series data from BPS and related sources. The study employs the Vector Error Correction Model (VECM) to examine both short- and long-term dynamics among the variables: agricultural productivity, rice prices, population size, and the food security index.Results: In the short term, agricultural productivity negatively affects food security due to yield instability. Higher rice prices positively impact food security by encouraging local production and competitiveness. Population growth, however, reduces food security by increasing demand. In the long term, both agricultural productivity and rice prices negatively affect food security, while population size shows a positive impact, possibly due to labor supply and market expansion. Conclusion: The study concludes that agricultural productivity, food prices, and population size influence food security in Indonesia differently in the short and long term. From an Islamic economic perspective, sustainable food security can be achieved through equitable welfare and fair distribution of food. Policies that promote increased agricultural productivity, food price stabilization, and sustainable population management are essential to ensuring sufficient food availability for all sectors of society. Therefore, the government must formulate policies that are more adaptive to demographic and economic changes to maintain Indonesia's food security.